Heterotopic Pancreas Presenting as Suspicious Mass in the Gallbladder - Foucault, Amélie; Veilleux, Hubert; Martel, Guillaume; Lapointe, Réal; Vandenbroucke-Menu, Franck (JOP. Journal of the Pancreas, 2012)
Context Heterotopic pancreas is a rare entity. Thirty-three cases in the gallbladder have been reported. We describe the first case of heterotopic pancreas mimicking a gallbladder cancer, identified within a calcified lesion in the thickened posterior wall of the gallbladder. Case report A 72-year-old woman with right upper quadrant pain was referred with a suspicion of gallbladder neoplasia. A CT scan demonstrated a 1 cm thickened posterior wall of the gallbladder with a 2 mm punctate calcification. An open cholecystectomy was carried out without complication. The frozen section demonstrated pancreatic tissue. Conclusion Heterotopic pancreas of the gallbladder is highly uncommon. It can mimic a neoplastic process in the gallbladder, particularly in the context of calcification. Its malignant potential in the gallbladder is unknown, in contrast to previously described neoplastic transformation with gastric heterotopic pancreas. Image: Gallbladder specimen with heterotopic pancreas.